Being, Flow and Knowledge in Māori Arts Education: Assessing Indigenous Creativity - Hindle, Rawiri; Hynds, Anne S.; Phillips, Hazel; Rameka, Lesley (The Australian Journal of Indigenous Education, 2015)
This article reflects on issues of Indigenous creativity in Māori arts education, along with what we see as problematic tensions of the assessment of intangible elements. Our writing is motivated by a desire to start a global dialogue on Indigenous/Māori epistemologies, pedagogies and ontologies, and the contradictions and tensions that threaten these through global assessment drives within schools. We argue that current student assessment regimes are being increasingly influenced by international neoliberal agendas, which focus on universal, measurable outcomes. By critically exploring the assessment of creativity in the arts from a Māori perspective, we reflect on several contradictions and tensions in current assessment drives within schools. In particular, the intangible dimensions of being and flow and their connection to creativity are examined, and we conclude with recommendations for further work in this area.